2017
DOI: 10.1111/aogs.13180
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D insufficiency, preterm delivery and preeclampsia in women with type 1 diabetes – an observational study

Abstract: Introduction. The aim of this study was to evaluate whether vitamin D insufficiency is associated with preterm delivery and preeclampsia in women with type 1 diabetes. Material and methods. An observational study of 198 pregnant women with type 1 diabetes. 25-Hydroxy-Vitamin D and HbA1c were measured in blood samples in early (median 8 weeks, range 5-14) and late (34 weeks, range 32-36) pregnancy. Kidney involvement (microalbuminuria or nephropathy) at inclusion, smoking status at inclusion, preterm delivery (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 34 publications
1
14
1
Order By: Relevance
“…Some studies in non-diabetic pregnant women have suggested that low total 25(OH)D is associated with contemporaneous [10] or subsequent PE [9,12], perhaps limited to early-onset disease [13]. Our present finding of no significant association is consistent with our previous study (that used different methodology to measure 25(OH)D) [30] and with a study by Vestgaard et al [17]. The present work extends those findings, showing that neither bioavailable nor free forms of 25(OH)D predicted PE, with the caveat that our cohort did not contain vitamin D-sufficient women.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Some studies in non-diabetic pregnant women have suggested that low total 25(OH)D is associated with contemporaneous [10] or subsequent PE [9,12], perhaps limited to early-onset disease [13]. Our present finding of no significant association is consistent with our previous study (that used different methodology to measure 25(OH)D) [30] and with a study by Vestgaard et al [17]. The present work extends those findings, showing that neither bioavailable nor free forms of 25(OH)D predicted PE, with the caveat that our cohort did not contain vitamin D-sufficient women.…”
Section: Discussionsupporting
confidence: 92%
“…By contrast, 25(OH)D, the standard metric for vitamin D, did not predict PE; of note, however, insufficient or deficient levels were almost universal in our diabetic cohort. Reported associations of vitamin D deficiency in diabetic pregnancy include preterm birth, increased T1DM rates in offspring of women with T1DM, and poor glycemic control [12,17,20,21,29]. Some studies in non-diabetic pregnant women have suggested that low total 25(OH)D is associated with contemporaneous [10] or subsequent PE [9,12], perhaps limited to early-onset disease [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Danish authors have reported a study of 198 pregnant women with type 1 diabetes; in the research group, insufficient vitamin D intake (<50 nmol/l) was observed in as many as 68 women (34%). [12] Vitamin D supplementation of 1500-2000 IU/d is recommended. [13]…”
Section: Gestational Diabetes Mellitusmentioning
confidence: 99%